Analisis Energi dan Eksergi Modul Surya 50 WP Tipe Polikristalin - Dwinanto, Matheus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
In this modern era, electricity has become a basic necessity so it is very necessary to sustain people lives and encourage economic growth in a region. The solar photovoltaic module has been used as a power plant in remote area thereby increasing the electrification ratio. In its operation the solar photovoltaic module generates electrical energy and thermal energy from the intensity of the solar radiation absorbed. One type of the solar photovoltaic module that is widely used is polycrystalline. This paper aims to examine the energy and exergy analysis of 50 WP solar photovoltaic module polycrystalline type based on sunny weather conditions for 4 days in October 2019 in Kupang. Experimental data is used to calculate the output power, exergy input, thermal exergy, electrical exergy, exergy loss, energy efficiency and exergy efficiency of the system. Increased the intensity of the solar radiation will increase the output power and exergy input but result in the exergy loss greater than thermal exergy and electrical exergy. The module surface temperature has a great influence on exergy efficiency. Energy efficiency is relatively constant, ranging from 19.6% to 19.9%. In contrast, the exergy efficiency is quite fluctuating, ranging from 42.09% to 54.19%